DISABILITY AND SOCIAL EXCLUSION IN THE LEGAL PROCESS: WOMEN AS VICTIMS OF SEXUAL VIOLENCE - Alhamudin Maju Hamonangan Sitorus (Marwah: Jurnal Perempuan, Agama dan Jender, 2022)
This article highlights the social exclusion against women with disabilities as a victim of sexual violence during the legal process. Unlike the previous study on people with disabilities which tend to discuss the social inequalities in the field of work, education, health, and political participation (Smith, 2003; Barnes & Mercer, 2005; Sakakibara, 2020; Temple et al., 2020; Dube et al., 2021), this study fills the gap on the legal aspect which has a lack of attention. This study contributes to methodological novelty through digital approach using NVIVO and Gephi Software. The data from online media news related to sexual violence against women with disabilities are analyzed using Textual Network Analysis (TNA). The findings show that women with disabilities as victims of sexual violence experienced social exclusion during the legal process. This article also provides an inclusive recommendation for the legal process of women with disabilities.